Implementation of remote units in two large out-of-hours emergency primary care districts in Norway - Erik Zakariassen; Steinar Hunskaar (Scandinavian Journal of Primary Health Care)
Objective An inter-municipal out-of-hours (OOH) district covers several municipalities with one centralized casualty clinic. These OOH districts are large geographical areas with long driving times to the casualty clinic. Remote OOH units were established in two OOH districts in Norway, to secure better access to the OOH service. Patients were offered video consultations with nurse-led appointments at the remote OOH units. The aim was to investigate contact rates and distribution of consultation types before and after the remote units were established. Design. An observational study with pre- and post-data collected from municipalities with and without (controls) remote OOH units.Setting Two OOH districts, Førde and Molde, with five and four remote OOH units, respectively.Subjects Inhabitants contacting the Local Emergency Communications Centers (LEMCs) in the two areas.Results In municipalities that established remote OOH units the contact rates to the LEMCs decreased by 15% in Førde and 16% in the Molde OOH districts in 2021, compared with 2019. Control municipalities had an increased rate of 7% and 2%, respectively. Consultation rates decreased by 16% and 12% in municipalities with remote OOH units in Førde and Molde, respectively. In 2021, 7% of contacts from municipalities with remote OOH units in Førde OOH district and 3% in Molde OOH district ended in a consultation at a remote OOH unit. In the Molde OOH district, where the traditional casualty clinic was replaced with remote OOH units, home visits and callouts decreased by 76% and 86% from 2019 to 2021.Conclusion Establishing remote OOH units could have decreased contact and consultation rates in both districts. Most contacts were handled with actions other than a remote OOH unit encounter with video consultation. There was a large reduction of home visits and callouts in the Molde OOH district in 2021, compared with 2019.